The Analysis of Associative Fields of Words-Stimuli МИР / МИР / МІР (PEACE) in East-Slavonic Languages - Terekhova, Diana (East European Journal of Psycholinguistics, 2014)
The free associative experiment is the traditional language awareness method of studying. Language consciousness investigations via associative experiments permit to represent the system of linguistic consciousness (not only the extent of a certain words in their reflections in mind) as a coherent and cohesive unit. It shows a unique picture of the world in each culture. The article is devoted to comparative psycholinguistic analyses of the associative fields of the words-stimuli МИР / МИР / МІР (peace). Common and specific features of the corresponding parts of the world reflection in minds of the Ukrainians, the Russians and the Byelorussians are described in it. Associative gestalt was used in our research to make a structure of all the research associative materials. The nuclear and periphery of the associative gestalt was defined in each language under analyses. The largest differences are found: 1) in different number of zones among three gestalts; 2) in existence of separate zones just in a certain gestalt in contrast to others; 3) in different zones’ degree that defines their rank and position in gestalts; 4) in quantitative and qualitative zones’ composition; 5) in gestalt kernels. References Tarasov, Ye. F. (2000). Aktualnye problemy analiza yazykovogo soznaniya [The key issues of the linguistic consciousness analysis]. Yazykovoye soznaniye i obraz mira. 24–33. Solovyova, N. V. (2005). Leksika voyni i mira v russkoy delovoy pismennosti kontsa XVI– XVII vv.: lingvokognitivniy aspect [The Lexis of War and Peace in Russian Business Documents of the Late XVI-XVII Centuries: Linguo-cognitive Aspect]. Minsk: Byelorussian State University. Stepanov, Yu. S. (2001). Konstanty: Slovar russkoy kultury [The Constants: Dictionary of Russian Culture]. Moscow: Akademicheskiy Proekt. Zhayvoronok V. V. (2006) Znaky ukrayinskoi etnokultury. [Signs of the Ukrainian Ethnoculture]. Kyiv: Dovira. Sternin, I. A., Bykova, G. V.(1998) Koncepty i lakoony [Concepts and Lacunes]. Yazykovoye soznaniye: formirovaniye i funkcionirovaniye, 33-39.